1992
DOI: 10.1063/1.463987
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of binary collision theories to complex molecules in simple liquids

Abstract: The relaxation dynamics of vibrationally excited ground-state azulene molecules have been examined by picosecond transient absorption spectroscopy in a variety of different solvents including hexane, chloromethanes, methanol, CClF3, Xe, and Kr. A high pressure optical cell was used to liquify gases for use as solvents and to change their density and temperature independently over the entire liquid density range. Experimental results indicate that the vibrational cooling rate is strongly solvent dependent, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…The second component with a lifetime of 11 ps agrees well with the lifetime of the longitudinal relaxation time of methanol ( % 9.2 ps) and hence can be assigned to the solvent reorganization process. [30,48] This assignment can only be confirmed by the results of analysis of the temporal profiles recorded at other wavelengths as well as in other alcoholic solvents (see below).…”
Section: Theoretical Calculationsmentioning
confidence: 72%
See 2 more Smart Citations
“…The second component with a lifetime of 11 ps agrees well with the lifetime of the longitudinal relaxation time of methanol ( % 9.2 ps) and hence can be assigned to the solvent reorganization process. [30,48] This assignment can only be confirmed by the results of analysis of the temporal profiles recorded at other wavelengths as well as in other alcoholic solvents (see below).…”
Section: Theoretical Calculationsmentioning
confidence: 72%
“…The possible reason behind this may be the choice of the probe molecules, which do not display much difference in fluorescence behavior in protic and aprotic solvents because of weak hydrogen-bonding interaction between the solute and solvent. [29][30][31][32][33] Recently, Morimoto et al studied the fluorescence quenching of a series of aromatic carbonyl compounds by alcoholic solvents. [23] This work revealed that the S 1 states of 3AF and 4AF are more efficiently quenched by alcohols than those of two coumarin dyes, namely, coumarin 153 (C153) and coumarin 151 (C151).…”
Section: Dipolar Solvation Versus Hydrogen-bonding Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it is wellestablished that both intra-as well as intermolecular hydrogen bonds act as accepting modes for the nonradiative electronic energy of the excited state, providing an efficient radiationless deactivation pathway, and its lifetime is strongly quenched [16][17][18][19][20][21][22][23]. The nature of coupling between the solute and the solvent molecules also governs the rate and mechanism of the transfer of excess vibrational energy of the excited state of the solute to the solvent bath [24][25][26][27]. Secondly, the hydrogen-bonding interaction between the solute and the solvent molecules in the first solvation cell also plays an important role in the dynamics of solvation, as well as the relaxation processes undergone by the excited states [10,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…J Pe(X,t) dX S(t) P eXt_)____ (6) f Pe(X,0) dX 16 Figure 15 shows S(t) for betaine in acetone assuming broadband excitation and selective excitation at 800 nm, 700 nm, and 640 nm. In all four cases, there is an induction period at early time during which the electron-transfer rate is very small.…”
Section: Selective Excitation Simulationsmentioning
confidence: 99%